Talking together in rural palliative care: a qualitative study of interprofessional collaboration in Norway - May-Lill Johansen; Bente Ervik (BMC, 2022)
Abstract Background Caring for people with palliative care needs in their homes requires close collaboration within and between primary and hospital care. However, such close collaboration is often lacking. Transitions of care are potentially unsafe and distressing points in a patient trajectory. Few studies have explored the experiences of healthcare professionals in the community who receive patients from hospital care and provide them with palliative care at home. Objective To explore how rural health professionals experience local and regional collaboration on patients in need of palliative care. Methods This was a qualitative focus group and interview study in rural Northern Norway involving 52 primary care health professionals including district nurses, general practitioners, oncology nurses, physiotherapists, and occupational therapists. Five uni-professional focus group discussions were followed by five interprofessional discussions and six individual interviews. Transcripts were analysed thematically. Results "Talking together" was perceived as the optimal form of collaboration, both within primary care and with specialists. Nurses and GPs had similar perceptions of their worst-case scenario in primary palliative care: the sudden arrival after working hours of a sick patient about whom they lacked information. These situations could be the result of a short notice transfer from secondary care or an emergency presentation after a crisis in patient management locally, the latter often resulting in a hospital admission. Participants missed timely and detailed discharge letters and in complex cases a telephone call or conference. Locally, co-location was perceived as advantageous for crucial communication, mutual support, and knowledge about each other's competencies and work schedule. Because local health professionals belonged to different units within the primary health care organisation, in some places they had limited knowledge about each other's roles and skill sets. Conclusions Lack of communication, both locally and between specialist and primary care, was a key factor in the worst-case patient scenarios for GPs and nurses working in primary palliative care in rural Northern Norway. Co-location of primary care professionals promoted local collaboration and should be encouraged. Hospital discharge planning should involve the receiving primary care professionals.